Tax avoidance and firm value: Unveiling the role of earnings management - Azalia, Amanda Izumi; Suciati, Puji Andrika; Firmansyah, Amrie (WIM Solusi Prima, 2024)
This research aims to test and analyze the effect of tax avoidance on company value with earnings management as a moderating variable in consumer goods sector companies listed on the Indonesia Stock Exchange. The object of this research is companies in the food and beverage sub-sector consumption sector during the 2020-2022 period, so there are 19 sample companies. The method used is linear regression with research results (1) Tax avoidance has a significant positive effect on company value (2) Tax avoidance has a significant effect on company value but not through earnings management. The earnings management variable cannot be used as a moderating variable model. (3) Earnings management cannot influence the relationship between tax avoidance and company value. The results of this research can then become a source of literature explaining the influence of tax avoidance on company value with earnings management as a moderating variable.